Changes in Prevalence and Severity of Domestic Violence During the COVID-19 Pandemic: A Systematic Review - Thiel, Freya; Büechl, Verena C. S.; Rehberg, Franciska; Mojahed, Amera; Daniels, Judith K.; Schellong, Julia; Garthus-Niegel, Susan (Frontiers in Psychiatry, 2022)
Background To contain the spread of COVID-19, governmental measures were implemented in many countries. Initial evidence suggests that women and men experience increased anger and aggression during COVID-19 lockdowns. Not surprisingly, media reports and initial empirical evidence highlight an increased risk for domestic violence (DV) during the pandemic. Nonetheless, a systematic review of studies utilizing participants' reports of potential changes in DV prevalence and severity during the pandemic as compared to pre-pandemic times is needed. Objective To examine empirical, peer-reviewed studies, pertaining to the potential change in prevalence and severity of different types of DV during the COVID-19 pandemic, as reported by study participants. Data Sources Electronic EMBASE, MEDLINE, PsycINFO, and CINAHL searches were conducted for the period between 2020 and January 5, 2022. References of eligible studies were integrated by using a snowballing technique. Study Selection A total of 22 primary, empirical, peer-reviewed studies published in English or German were included. Results Of the 22 studies, 19 were cross-sectional whereas 3 included both pre-pandemic and during pandemic assessments. Data synthesis indicates that severity of all types of DV as well as the prevalence of psychological/emotional and sexual DV increased for a significant number of victims in the general population during the pandemic. Evidence for changes in prevalence regarding economic/financial, physical, and overall DV remains inconclusive. There was considerable between-study variation in reported prevalence depending on region, sample size, assessment time, and measure. Conclusions Data synthesis partly supports the previously documented increase in DV. Governmental measures should consider the availability of easily accessible, anonymous resources. Awareness and knowledge regarding DV need to be distributed to improve resources and clinical interventions.